Endophytic Fungi of Marine Alga From Konkan Coast, India—A Rich Source of Bioactive Material - Kamat, Siya; Kumari, Madhuree; Taritla, Sidhartha; Jayabaskaran, C. (Frontiers in Marine Science, 2020)
Endophytes are an unexploited source of pharmacologically relevant compounds owing to their species richness and diversity. In this study, a total of twenty-six endophytic fungi were isolated and identified from ten marine algal samples collected from Konkan coast, Goa, India. Eighteen of the fungal isolates belonged to phylum Ascomycota while one belonged to phylum Basidiomycota based on ITS sequencing. Further, the genus Aspergillus sp. was the most common and abundant endophyte found in the sampled algal species. A significant antibacterial activity against five pathogenic bacteria was exhibited by the extracts of fungal isolates AG1.1, AG1.1 (G) and VG2.6 (agar diffusion assay). The extracts of fungal endophytes VB1.1, PG1.2 and VG2.6 demonstrated good antioxidant activity (DPPH scavenging assay). Further, cytotoxicity of all the endophytic extracts on human cancer cell lines was determined by MTT and resazurin assay. Crude extract of Aspergillus unguis (AG 1.2) showed the highest cytotoxic potential on cervical cancer (HeLa), breast cancer (MCF-7), lung cancer (A549) and skin cancer (A431) cell lines in a concentration dependent manner. Moreover, Gas Chromatography-Mass Spectroscopy analysis of the extract of A. unguis (AG 1.2) confirmed presence of several bioactive metabolites including azelaic acid, azetidine and furopyrans. The extract of A. unguis (AG 1.2) demonstrated G1 phase cell cycle arrest, reactive oxygen species (ROS)-dependent MMP loss and apoptosis-dependent cell death in A431 cells. The algae-derived fungal endophytes of Konkan coast are a rich source of novel pharmaceutically active compounds is indicated by this work.